2012
DOI: 10.1371/journal.pone.0031882
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signalling Pathway Parameters for Mammalian Cells

Abstract: Wnt/β-catenin signalling regulates cell fate, survival, proliferation and differentiation at many stages of mammalian development and pathology. Mutations of two key proteins in the pathway, APC and β-catenin, have been implicated in a range of cancers, including colorectal cancer. Activation of Wnt signalling has been associated with the stabilization and nuclear accumulation of β-catenin and consequential up-regulation of β-catenin/TCF gene transcription. In 2003, Lee et al. constructed a computational model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(134 citation statements)
references
References 75 publications
11
120
3
Order By: Relevance
“…These observations suggest that other FAM83 members that also bind CK1α probably account for the enhanced nuclear pool of CK1α 31. Because most of the β‐catenin protein is reported to be associated with the plasma membrane 41, 42, we assessed the effect of PAWS1‐loss on membrane‐associated pool of β‐catenin. We also found high levels of total β‐catenin in the plasma membrane fractions and quite substantial amounts in the cytoskeletal fractions, when compared to cytoplasmic and nuclear fractions (Fig EV5E).…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggest that other FAM83 members that also bind CK1α probably account for the enhanced nuclear pool of CK1α 31. Because most of the β‐catenin protein is reported to be associated with the plasma membrane 41, 42, we assessed the effect of PAWS1‐loss on membrane‐associated pool of β‐catenin. We also found high levels of total β‐catenin in the plasma membrane fractions and quite substantial amounts in the cytoskeletal fractions, when compared to cytoplasmic and nuclear fractions (Fig EV5E).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the association between catenin and cancer has become well known and the number of studies on the association between cell adhesion molecules and malignant behavior has increased (7,8). β-catenin is an important multifunctional cytoplasmic protein, which was initially considered as an intracellular molecule on the cell membrane that interacted with the calcium-dependent adhesion molecule E-cadherin (9).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of two mammalian kidney cell lines have shown that Axin concentrations are in the range 110 -150 nM; total and cytosolic b-catenin concentrations are in the hundreds and tens of nM range, respectively (Tan et al 2012). APC is found at 12 -40Â lower concentrations than Axin in these cells.…”
Section: E C I S S a M P K 2003 C H E E E E R P T N Y S I K Y N E E 1mentioning
confidence: 99%
“…However, the APC interaction mediated by the RGS domain is dispensable when Axin is overexpressed in SW480 colon cancer cells (see below) (Kohler et al 2009;Roberts et al 2011). Measurements of destruction complex components in mammalian kidney epithelial cells and Xenopus oocytes gave different absolute and relative concentrations of APC and Axin (Salic et al 2000;Lee et al 2003;Tan et al 2012), suggesting that Wnt signaling operates over a range of component concentrations that vary with cell type. Studies in Drosophila have suggested that precise APC levels are important in modulating Wnt responses; a twofold change in APC2 was shown to profoundly affect signaling in photoreceptor development, indicating that APC levels are likely tuned to optimize responses to morphogen gradients .…”
Section: Axin the Central Phosphorylation Scaffoldmentioning
confidence: 99%